EDUCATION AS A DOMINANT SCOPE HUMAN DEVELOPMENT - Бервено, О. В. (Bulletin of V. N. Karazin Kharkiv National University Economic Series, 2019)
The purpose of article - revealing the role of education in the new social and cultural realities. Disclosed the relationship of education and human development, education and quality of life. The content of education is shown through the exercise of the basic functions. The main impacts of education on human and socio-economic development, the main tasks of its reform.